Gestational, perinatal, and postnatal factors that interfere with practice of exclusive breastfeeding by six months after birth - Mariana Moraes de Oliveira; José Simon Camelo (International Breastfeeding Journal, 2017)
Abstract Background Despite evidences indicating the superiority of breastfeeding and recent advances in the indicators of breastfeeding in Brazil, exclusive breastfeeding (EBF) during the first six months after birth continues to be an infrequent practice in the country. The objective of the present study was to determine which gestational, perinatal, and postnatal factors of the mother-baby dyad might be associated with the cessation of EBF by six months after birth. Methods Data were collected at the rooming-in facility of the Reference Center of Women’s Health of Ribeirão Preto-Mater (CRSM-Mater) during the postpartum period (24 to 72 h after birth) from December 2012 to April 2013 and by telephone contact between the researcher and participating mothers by six months after birth. Questionnaires were applied to collect data, such as the practice of EBF in the last 24 h in the sixth month after birth. The hierarchical theoretical model was proposed and data were analyzed statistically by log-binomial regression models using SAS 9.3. Results The study involved 283 mother-baby dyads in which the mother evaluated did not present pregnancy-puerperal complications that could impede breastfeeding and confirmed the interest in breastfeeding her child. After the telephone contact in the exact sixth month after the birth of each participating baby, 84.8% of the participating mothers reported that they were no longer exclusively breastfeeding their babies. After statistical analysis, we found that there was a significant association between cessation of EBF and maternal report of previous experience with EBF for one month (0.91, 95% CI 0.81, 0.99) and six months (0.81; 95% CI 0.68, 0.94). These practices were associated with the maintenance of EBF and, even after adjustment for maternal socio-demographic variables, this association was maintained (0.85; 95% CI 0.73, 0.99). Thus, there is a greater chance of practicing and maintaining EBF by six months after birth when mother had previous experience with it. Conclusion The identification of the risk variables associated with cessation of EBF by six months postpartum, such as previous experience with exclusive breastfeeding, may contribute to the effectiveness of EBF intervention and support measures during the first six months after birth.